Irish Public Health Nursing Services and Home Support Services: governance of older persons' home care. Issue 1 (8th December 2021) - McDonald, Anne; Frazer, Kate; Warters, Austin
Abstract: Objective: To describe experiences of nurses in the Irish Public Health Nursing service working with Home Support Services (HSS) when providing home care for older people. Design: Qualitative design. Two of twenty‐four focus groups undertaken in 2018 are examined to report specific experiences of registered nurses. Sample: The first group comprised three Public Health Nurses (PHNs) and two community Registered General Nurses (cRGNs) and the second comprised three PHNs and one cRGN. In total nine nurses participated. Measurements: Focus group interviews were used to collect data, discussions lasted 60–90 minutes and were audio‐recorded, professionally transcribed verbatim, and anonymised. Results and conclusions: Gaps in lines of authority and accountability in day‐to‐day care exist, posing risks to safety. Establishing an enhanced home care model for complex cases and levels of accountability and supervision is critical. Investigating ways of adopting digital solutions to share commissioned home care plans with primary care teams (PCTs) would clarify responsibility and roles and reduce the risks of care left undone. Formally defining the role of commissioned home care agencies in primary care and that which they are expected to play during times of crisis, such as during COVID‐19 pandemic will enhance integrated care and governance.